Foraminíferos bentónicos recientes en sedimentos de fondo de la cuenca de panamá (pacífico colombiano), como indicadores de productividad y oxigenación (2003)
Thirteen deep-sea samples (core-tops) from the Panama Basin, Colombian Pacific, were analysed for benthonic foraminifera in the >150µm size fraction. Based on the microfaunal content, three zones are recognised in the Panama Basin: (1) northern euphrophic region (~8° to 5,5°N), characterized by a high concentration of organic matter flux to the seafloor, oxygenated sediments, and influence of the Panama Bight and the Costa Rica Dome upwelling systems, (2) mesotrophic region (~5,5 to 2°N), characterized by low fluxes of organic carbon to the seafloor, oxygenated sediments, terrigenous influence and fluctuations of the upwelling systems of the basin, and (3) southern euphotic region (south of ~2°N), characterized by a larger organic carbon flux to the seafloor, low oxygen content (disoxia) and influence of the Equatorial Divergence.